THE USE OF METHODS OR MEANS OF WARFARE WHICH CAUSED DAMAGE TO THE NATURAL ENVIRONMENT BASED ON THE INTERNATIONAL HUMANITARIAN LAW - Muhammad Ryan Dwi Saputra (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract Environment has been widely recognized as international interest and all states shall avoid any activities that may damage the environment. The adoption of Stockholm Declaration 1972, World Charter for Nature 1982, and Rio Declaration 1992 denotes that protection of the environment reflects customary international law. War or armed conflict was one of the principal contributors to the environmental damages. As in the Vietnam War, the United States attempted to create artificial rain by seeding the cloud which led to the establishment of the 1976 Convention on the Prohibition of Military or Any Hostile Use of Environmental Modification Techniques (ENMOD Convention) and the Additional Protocol I 1977. However, the Gulf War 1990-1991 gave rise to the questions whether those two instruments were sufficient to encompass the environmental damages caused by the Iraqi methods of warfare by burning oil wells and spilling oil to the sea. This issue was raised by the author since these two instruments set a high threshold and unclear terms on a degree of environmental damages to be considered as a violation. Accordingly, this paper discusses whether the environmental damages caused by the Persian Gulf War meets the threshold set by the Additional Protocol I and the ENMOD Convention, and further discusses the international responsibility that arose from the damages caused by the War. The result of this research shows that environmental damages caused by Iraqi burning oil wells and oil spill apparently did not satisfy the threshold set by the Additional Protocol I and the ENMOD Convention. Keywords: Armed Conflict, Environment, Gulf War, International Humanitarian Law, Responsibility Abstrak Lingkungan sudah diakui sebagai permasalahan internasional dan semua negara wajib untuk menghindari kegiatan yang berakibat kerusakan terhadap lingkungan. Pembentukan Deklarasi Stockholm 1972, Piagam Dunia Untuk Lingkungan 1982 dan Deklarasi Rio 1992 menunjukkan bahwa perlindungan terhadap lingkungan telah merefleksikan hukum kebiasaan internasional. Perang atau konflik bersenjata merupakan salah satu penyebab utama kerusakan lingkungan. Seperti percobaan untuk membuat hujan buatan yang dilakukan oleh Amerika Serikat dalam Perang Vietnam yang berujung dibentuknya Convention on the Prohibition of Military or Any Hostile Use of Environmental Modification Techniques 1976 (Konvensi ENMOD) dan Protokol Tambahan I 1977. Namun, Perang Teluk 1990-1991 menimbulkan pertanyaan apakah kedua instrumen tersebut dapat mencakup kerusakan lingkungan yang diakibatkan oleh metode berperang Irak dengan membakar dan menumpahkan minyak. Permasalahan tersebut diangkat oleh penulis karena kedua instrumen tersebut menetapkan kriteria kerusakan lingkungan yang kurang jelas dan standar yang terlalu tinggi untuk dinyatakan sebagai pelanggaran. Oleh karena itu, penelitian ini akan membahas apakah kerusakan lingkungan yang diakibatkan oleh Perang Teluk memenuhi syarat yang ditetapkan oleh Protokol Tambahan I dan Konvensi ENMOD, dan juga membahas tanggung jawab internasional yang timbul sebagai akibat dari kerusakan lingkungan yang diakibatkan oleh perang. Hasil penelitian menunjukkan bahwa kerusakan lingkungan yang diakibatkan oleh Irak dengan membakar dan menumpahkan minyak ternyata tidak memenuhi standar yang ditetapkan oleh Protokol Tambahan I dan Konvensi ENMOD. Kata kunci: Hukum Humaniter Internasional, Konflik Bersenjata, Lingkungan, Perang Teluk, Pertanggungjawaban